Regulación jurídica de la actividad económica - Spinelli, Armando P. (1957)
There is a tendency to consider more and more the private economic situation as a public problem and of public concern, which results in the necessity for the State to change substantially its aims and concerns. This movement, called economic rationalization, concertation or concentration, by which the State, surpassing the classical limits of intervention, directs the private activities in accordance with a conscient plan, presents itself in two typical forms: that of a country which, for economic or political reasons has already an ample and total organization, and that of others which have to create firstly the conditions which make this impulse to be felt. The author analyses the situation of several countries belonging either to the first or to the second group. In Argentina, this has been discussed from the judicial point of view, by the Fourth National Congress of Lawyers which included as point 7º of their deliberations the "Judicial regulation of industrial activities".